Use of ultra‐high molecular weight polycaprolactone scaffolds for ACL reconstruction. Issue 5 (5th November 2015) - Leong, Natalie L.; Kabir, Nima; Arshi, Armin; Nazemi, Azadeh; Jiang, Jie; Wu, Ben M.; Petrigliano, Frank A.; McAllister, David R.
ABSTRACT: Previously, we reported on the implantation of electrospun polycaprolactone (PCL) grafts for use in ACL tissue engineering in a small animal model. In the present study, we hypothesized that grafts fabricated from ultra‐high molecular weight polycaprolactone (UHMWPCL) would have similarly favorable biologic properties but superior mechanical properties as compared to grafts fabricated from PCL. Two forms of polycaprolactone were obtained (UHMWPCL, MW = 500 kD, and PCL, MW = 80 kD) and electrospun into scaffolds that were used to perform ACL reconstruction in 7–8 week old male Lewis rats. The following groups were examined: UHMWPCL, PCL, flexor digitorum longus (FDL) allograft, native ACL, as well as sham surgery in which the ACL was transsected. At 16 weeks post‐operatively, biomechanical testing, histology, and immunohistochemistry (IHC) were performed. Analysis of cellularity indicated that there was no significant difference among the UHMWPCL, PCL, and FDL allograft groups. Quantification of birefringence from picrosirius red staining demonstrated significantly more aligned collagen fibers in the allograft than the PCL group, but no difference between the UHMWPCL and allograft groups. The peak load to failure of the UHMWPCL grafts was significantly higher than PCL, and not significantly different from FDL allograft. This in vivo study establishes the superiority of the higher molecular weight version of polycaprolactone over PCL as a scaffold material for ACL reconstruction. By 16 weeks after implantation, the UHMWPCL grafts were not significantly different from the FDL allografts in terms of cellularity, peak load to failure, stiffness, and collagen fiber alignment. © 2015 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 34:828–835, 2016.